Prostanoid (FP) receptor polymorphisms : the association of novel single nucleotide polymorphism with the responsiveness of glaucoma patients to topical latanoprost - Ong, Chieng Lee Ling@Lee (2006)
Introduction: Diversity in clinical response among glaucomatous patients in response to topical latanoprost is not a new issue, many researchers attributing it to the different races, treatment regimes, glaucoma types, and some genetic variants. Objective: The objective of this study is to determine the presence of polymorphism in exon of PTGFR gene and its role in responsiveness of glaucoma patients to topical latanoprost treatment. Methodology: Glaucoma patients started on topical latanoprost were followed up for 6 months. Pattern of lOP and rate of good responder (30% reduction or more), moderate responder (15-30% reduction) and poor responder (less than 15% reduction) were determined. Polymorphism of the PTGFR protein coding region was identified among the glaucoma patients and the controls using denaturing High Performance Chromatography ( dHPLC). The identified polymorphisms were associated with glaucoma and the pressurelowering effect of topicallatanoprost among glaucomatous patients on treatment. Result: From 76 glaucoma patients and controls screened, no exon SNP was found. One novel intron nSNP<A-T) at 5'flanking region of exon-3 with frequency of 46% was identified. Among the glaucoma patients, mean lOP reduction was 33.1% and there was as high as 47.4% good responder, 28.9% of moderate responder and 23.7% of poor responder. The lntron SNP was statistically found to be neither associated with the responder rate, the race nor with glaucoma patients. Conclusion: Topical latanoprost is effective among glaucoma patient in our local set up. The novel intron SNP found within the PTGFR gene does not statistically associate with glaucoma and clinical lOP lowering effect among glaucoma patients receiving topical latanoprost.